1993
DOI: 10.1017/s0043174500052188
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Aqueous Chlorimuron and Imazaquin in the Presence of Phenolic Acids and Riboflavin

Abstract: Laboratory experiments were conducted to determine the effect of three phenolic acids, acetone, and riboflavin on aqueous photolysis of chlorimuron and imazaquin. The phenolic acids investigated were caffeic acid (CA), ferulic acid (FA), andp-coumaric acid (PCA). Treatment solutions were contained in quartz vessels and irradiated with 300 to 400 nm UV light in a photoreactor. The extrapolated photolysis half-life of chlorimuron in pure solution was 107 h, compared to a half-life of 0.42 h for pure aqueous imaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Chlorimuron-ethyl degrades in the agricultural environment primarily via pH-and temperature-dependent chemical hydrolysis (Beyer et al, 1988;Brown, 1990;Hay, 1990), as observed for many sulfonylurea herbicides, such as sulfometuron-methyl (Harvey et al, 1985), chlorsulfuron (Sabadie, 1990), metsulfuron-methyl (Sabadie, 1991), rimsulfuron (Schneiders et al, 1993), nicosulfuron (Sabadie, 2002 and flazasulfuron (Bertrand et al, 2003). The phototransformation of chlorimuron by sunlight also takes place on the soil surface (Choudhury & Dureja, 1996 a) and in water (Venkatesh et al, 1993;Choudhury & Dureja, 1996 b). Within the surface soil chlorimuron is also considered to serve as a source of carbon, nitrogen and sulfur for microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorimuron-ethyl degrades in the agricultural environment primarily via pH-and temperature-dependent chemical hydrolysis (Beyer et al, 1988;Brown, 1990;Hay, 1990), as observed for many sulfonylurea herbicides, such as sulfometuron-methyl (Harvey et al, 1985), chlorsulfuron (Sabadie, 1990), metsulfuron-methyl (Sabadie, 1991), rimsulfuron (Schneiders et al, 1993), nicosulfuron (Sabadie, 2002 and flazasulfuron (Bertrand et al, 2003). The phototransformation of chlorimuron by sunlight also takes place on the soil surface (Choudhury & Dureja, 1996 a) and in water (Venkatesh et al, 1993;Choudhury & Dureja, 1996 b). Within the surface soil chlorimuron is also considered to serve as a source of carbon, nitrogen and sulfur for microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The total UV energy emitted under each light regime was monitored during each 2,4-D PHOTODEGRADATION IN WATER 475 experiment by trifluralin-acetonitrile chemical actinometry (Draper, 1987;Venkatesh et al, 1993). The actinometer was calibrated in a merry-go-round photoreactor apparatus fitted with lamps having a known energy output and 300-400 ran wavelength distribution (Draper, 1987, Venkatesh et al, 1993.…”
Section: Methods Common To All Experimentsmentioning
confidence: 99%
“…The actinometer was calibrated in a merry-go-round photoreactor apparatus fitted with lamps having a known energy output and 300-400 ran wavelength distribution (Draper, 1987, Venkatesh et al, 1993.…”
Section: Methods Common To All Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imazaquin can persist in the soil for up to seven months and can interfere with soil microbes sensitive to this chemical. Its degradation in the environment is partly through photo-decomposition (VENKATESH et al 1993) and microbial action, but its fate still remains unclear (RODRIGUES and ALMEIDA 1995). In Brazil, imazaquin is registered for use with soybean cultivation, and is commercially available as Scepter ® and Topgan ® in the form of soluble concentrate or dispersible granules, respectively.…”
mentioning
confidence: 99%